Assessment of legislation and practices for the sustainable management of waste electrical and electronic equipment in India. (October 2017) - Pathak, Pankaj; Srivastava, Rajiv Ranjan; Ojasvi,
Abstract: The waste electrical and electronic equipment (WEEE or e-waste) are the globally recognized hazardous material, though containing a full spectrum of valuable and critical metals. India, being the fifth largest generator of WEEE, is facing a great challenge in the sustainable management of such waste. Therefore since the past few years, Government of India has been trying to establish a proper institutional and legislative framework to implement the sustainable management of WEEE in the country. Accordingly, the global issues related to WEEE and how it is being tackled by other countries/regions with implemented regulations has been reviewed in this paper. Furthermore, the status-quo of WEEE generation, management policies and recycling practices in India has been systematically assessed while emphasizing the key issues of future initiatives, environmental and health hazards. The mathematical model of WEEE generation in India along with identifying the influences of recycling in sustainable management of WEEE has also been established.